Analysis of Sustainability Report Disclosure and Sustainability Performance in Energy, Oil, and Gas Cluster State-Owned Enterprises - Harbi Ash Shidiq; Adam Zakaria; Hafifah Nasution (PT. BATARI EDU CALYA, 2024)
This study aims to analyze the level of Sustainability Report (SR) disclosure and sustainability performance of PT Perusahaan Listrik Negara (Persero) and PT Pertamina (Persero), two major State-Owned Enterprises (SOEs) operating in the energy, oil, and gas cluster in Indonesia. A descriptive quantitative approach was employed, utilizing content analysis of Sustainability Reports for the 2021–2022 period. The variables examined include Sustainability Report disclosure and sustainability performance measured through economic, environmental, and social indicators. The findings indicate a positive trend in SR disclosure. PT PLN increased its disclosure rate from 84% in 2021 to 88% in 2022, while PT Pertamina improved from 88% in 2021 to 100% in 2022. These results reflect a strengthened corporate commitment toward transparency, accountability, and sustainable business practices. This research contributes to the literature on sustainability reporting and performance in Indonesian SOEs, particularly within high-impact industries. The findings underscore the strategic importance of sustainability performance in enhancing corporate reputation and stakeholder trust.